Prediction of new chromene-based inhibitors of tubulin using structure-based virtual screening and molecular dynamics simulation methods. (December 2017) - Aryapour, Hassan; Dehdab, Maryam; Sohraby, Farzin; Bargahi, Afshar
Graphical abstract: Highlights: A mixed computational method was carried out to identify chromene-based inhibitors of tubulin. After the virtual screening, the hit compounds were identified: PubChem CID: 16814409, 17594471, 57367244 and 69899719. Hit compounds show identical and even better activity than colchicine and therefore can be potential inhibitors of tubulin polymerization. Hit compounds significantly suppressed the dynamic instability of microtubules compared to apo-tubulin. Abstract: Multidrug resistance (MDR) is one of the serious problems in cancer research that causes failure in chemotherapy. Chromene-based compounds have been proven to be the novel anti-MDR agents for inhibiting proliferation of tumor cells through tubulin polymerization inhibition of by binding at the colchicine binding site. In this study, we screened a chromene-based database of small molecules using physicochemical, ADMET properties and molecular docking to identify potential hit compounds. In order to validate our hit compounds, molecular dynamics simulations and related analysis were carried out and the results suggest that our hit compounds (PubChem CIDs: 16814409, 17594471, 57367244 and 69899719) can prove to be potential inhibitors of tubulin. The in silico results show that the present hits, like colchicine, effectively suppressed the dynamic instability of microtubules and induced microtubule-depolymerization and cell cycle arrest.